The effectiveness of using geometers sketchpad (gsp) in the teaching and learning of Mathematics in a Malaysian technical school (IR) - Rohaiza Ramli (2015)
The purpose of this study was to determine the effectiveness of an interactive geometry software program, Geometers Sketchpad (GSP), in the teaching and learning of mathematics among technical schools students. The quasi-experimental study was conducted on 56 students from a randomly selected technical school. The students were assigned into a controlled and an experimental group using cluster (class-based) random sampling. The control group received conventional teaching method while the experimental group was taught using a GSP module on a chosen topic namely Trigonometric Functions for the duration of 8 weeks. Three sets of tests, which are pre-test, post-test and retention-test were administered to both groups of students in weeks 1, 8 and 10, respectively. Besides the tests, a set of questionnaires and an interview protocol were used in collecting the empirical data. The results of tests and questionnaires were analysed using descriptive and inferential statistics such as mean, standard deviation and independent t-test. The findings indicated that there were improvement in the mean scores for both groups, with the experimental group gained significantly higher. The result of the retention-test showed that retention ability of knowledge acquired by the experimental group was significantly better compared to the control group. Thus, the study concludes that the use of GSP as a tool in the teaching and learning of mathematics has improved the students' achievement and retention ability. In addition, the students and the teacher have demonstrated positive attitudes and enthusiasm in this new learning approach. The findings also supported the theories and models used in the conceptual framework of this study. The implication derived from the study is that GSP can be utilised as a very effective tool to enhance mathematics teaching and learning. Finally, the study recommends that the ministry should be devising an effective way to secure teachers commitments in using GSP in teaching mathematics especially in technical schools.